Phantasy, Image Consciousness, and Memory (1898-1925) - Husserl, Edmund; Brough, John B. (Dordrecht : Springer, 2005)
Cover -- Contents -- Translator's introduction -- No. 1. Phantasy and image consciousness (Third Principal Part of the Lectures from the Winter Semester 1904/05 on "Principal Parts of the Phenomenology and Theory of Knowledge") -- Chapter 1. The Question of Phantasy Presentation in Contrast to Perceptual Presentation -- 1. Ambiguity of the concept of phantasy in ordinary language - phantasy experience as the foundation of phenomenological eidetic analysis and concept formation -- 2. The task of acquiring an essentially unitary concept of phantasy presentation as phantasy apprehension - characterization of perceptual apprehension -- 3 The failure of contemporary psychology's inquiry into the question of the relationship between perceptual presentation and phantasy presentation. Absence of the concept of objectivating apprehension -- 4. Brief presentation and criticism of Brentano's theory of "presenting" -- 5. The question of the difference between perceptual presentation and phantasy presentation and the particular problem of the distinction between the corresponding apprehension contents: sensation and phantasm -- 6. Critical discussion of the differences between perception and phantasy put forward by the psychologists -- Chapter 2. Interpretation of Phantasy Presentation as Image Presentation (Imagination) just like Physical Image Presentation -- 7. Kindred distinctions within perceptual apprehension and phantasy apprehension -- 8. Phantasy presentation as pictorialization. Beginning the process of defining the essence of image presenting -- 9. Physical imagination as a parallel case to phantasy presentation -- 10. The community of essence between physical imagination and ordinary phantasy presentation with respect to "mental images" -- 11. The relation to the image subject, or the two apprehensions, one built on the other, in phantasy presentation reference to a precise analogue: word appearance as carrier of a second apprehension as sign -- 12. The presu
boek
Keywords: Husserl, Edmund